Pengaruh Self Concept tehadap Kematangan Karir Mahasiswa Penerima Beasiswa KIP di Kota Bandung - Putri Julieta Yasmine; Yuli Aslamawati (Bandung Conference Series: Psychology Science, 2024)
Abstract. Individuals with low SES have limited range of aspirations in planning their career choices. However, students from lowest SES with positive Self Concept can achieve high Career Maturity compared to students with other SES strata. This study aims to examine how much contribution Self Concept has on Career Maturity of KIP Scholarship Students in Bandung. The data was collected using Google Form with a non-purposive snowball sampling technique to students (N = 100) aged 18-25 years who are currently pursuing Higher Education in Bandung. Self Concept were measured using the AF5 (Five-Factor Self-Concept) scale developed by Garcia-Grau et al (2014) which has been adapted into Indonesian by Putri (2020). Career Maturity were measured using the Career Maturity scale compiled by Dewi Sartika (2003) in Hadisti (2021). Linear regression analysis was used to examine how much contribution Self Concept has on Career Maturity with a determination coefficient value of 0.302, which has contibuted 30.2% with a Sig value of 0.007 (Sig. <0.05), which means that there is a significant contribution of the Self Concept variable on Career Maturity. Schools and universities need to pay attention to be able to provide effective career guidance so that students with low SES can show high Career Maturity. Abstrak. Individu dengan SES yang rendah memiliki jangkauan aspirasi yang lebih sempit dalam merencanakan pilihan karir mereka. Namun mahasiswa dari SES terendah dengan Self Concept yang positif dapat memperoleh Kematangan Karir yang tinggi dibandingkan dengan Mahasiswa dengan strata SES lainnya. Penelitian ini bertujuan untuk menguji seberapa besar pengaruh Self Concept terhadap Kematangan Karir Mahasiswa Penerima Beasiswa KIP di Kota Bandung. Pengambilan data dilakukan menggunakan Google Form dengan teknik sampling non purposive snowball kepada Mahasiswa (N=100) berusia 18-25 tahun yang sedang melaksanakan Pendidikan Tinggi di Kota Bandung. Self Concept diukur dengan AF5 (Five-Factor Self-Concept) scale yang dikembangkan oleh Garcia-Grau et al (2014) yang telah diadaptasi ke Bahasa Indonesia oleh Putri (2020). Kematangan Karir diukur dengan menggunakan skala Kematangan Karir yang disusun oleh Dewi Sartika (2003) dalam Hadisti (2021). Analisis regresi linier digunakan untuk menguji seberapa besar pengaruh Self Concept terhadap Kematangan Karir dengan nilai koefisien determinasi sebesar 0.302 yaitu berpengaruh sebesar 30.2% dengan nilai Sig 0.007 (Sig.<0.05) yang artinya terdapat pengaruh yang signifikan dari variabel Self Concept terhadap Kematangan Karir. Perlu diperhatikan oleh sekolah dan Perguruan Tinggi untuk dapat memberikan bimbingan karir yang efektif agar siswa dan Mahasiswa dengan SES yang rendah agar dapat menunjukkan Kematangan Karir yang tinggi.